Utilization of social franchising in family planning services: a Pakistan perspective - Nayab; Ahmad, Taimoor; Fatmee, Areesh; Sajjad, Ibtisam; Usmani, Zona; Khan, Ayesha; Shahzad, Sara; Khan, Adnan Ahmad (Frontiers in Global Women's Health, 2024)
Pakistan's private sector caters to around 65% of family planning users. Private sector family planning was promoted in the Delivering Accelerated Family Planning in Pakistan (DAFPAK) program by UK's Foreign, Commonwealth & Development Office (FCDO) in 2019. We use data from DAFPAK to analyze the clientele and products distributed by two major NGOs, Marie Stopes Society (MSS) and DKT Pakistan, that support private providers in Pakistan. We also examined the effect of COVID-19 on client visits and contraceptives uptake at private facilities in Pakistan.DAFPAK used field validation surveys to analyze the volume of clients and products of 639 private facilities across three provinces (Punjab, KPK and Balochistan) of Pakistan. The data was collected in two phases (February 2020 and 2021) using multi-stage cluster sampling at 95% confidence level. Using a generalized negative binomial regression, facility-level characteristics and impact of COVID-19 was analyzed with the volume of clients and products given out at 95% confidence interval alongside descriptive analysis.DKT facilities covered 53% of the sample while MSS covered 47%, with 72% facilities in the rural areas. Average facility existence duration is 87 months (7.25 years). While the average experience of the facility staff is 52 months (4.33 years). MSS is serving more clients as compared to DKT during both phase 1 (IRR: 3.15; 95% CI: 2.74, 3.61) and phase 2 (IRR: 2.11; 95% CI: 1.79, 2.49). Similarly, MSS had a greater volume of products given out in both phases 1 (IRR: 1.89; 95% CI: 1.51, 2.38) and phase 2 (IRR: 2.57; 95% CI: 2.09, 3.14). In both phases, client visits and product distribution decreased when client privacy is invaded (IRR: 0.74; 95% CI: 0.67, 0.82phase 1) and (IRR: 0.83; 95% CI: 0.72, 0.97phase 2). Lastly, during COVID-19, products distribution decreased by a factor of 0.84 (IRR: 0.84; 95% CI: 0.72, 0.97) but client visits remain unaffected.Overall, clientele is low for all facilities. At a facility, privacy is a determinant of client visits and products given out per visit. Transiently, during COVID-19, client volumes decreased, with a shift from oral pills to condoms and emergency contraceptive pills.